PERANCANGAN SISTEM INFORMASI E-RAPOR BERBASIS WEB DI SMK MUHAMMADIYAH 1 PADANG - Fitma Fiana Anggraini; Irsyadunas Irsyadunas; Satrio Junaidi (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This research aims to develop a web-based E-Report Information System that can simplify the process of reporting grades at SMK Muhammadiyah 1 Padang. The methodology used in this research is the Software Development Life Cycle (SDLC) with an iterative model, which includes the stages of planning, analysis, design, implementation, testing and evaluation. Beta testing involves experts and end users. The assessment results from experts show an average percentage of 92.82% in the very good category, while assessments from users get an average percentage of 91.12% which is also categorized as very good. Based on the results of this test, the E-Report Information System developed was declared valid and suitable for use to simplify the process of reporting student grades at SMK Muhammadiyah 1 Padang.